ETOS KERJA STEBIS IGM DI SEKOLAH TINGGI EKONOMI DAN BISNIS SYARIAH (STEBIS) INDO GLOBAL MANDIRI PALEMBANG - Ulpa Dwiyanti; Meriyati Meriyati (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
Work ethic is said to be a determining factor for the success of individuals, groups, institutions and also the widest part of the nation in achieving its goals. The implementation of public administration is also influenced by the work ethic possessed by public officials in carrying out the needs of society. Work ethic is the main thing in carrying out work to achieve excellence in character and excellence of character that results in superior work and performance. Of course, these advantages come from the fruit of a human's perseverance. The ability to live work is very important in an effort to create excellence. The point is that when we do a job, we are essentially doing a service process. Living up to work as a service requires transcendent abilities that go beyond the small human space. This can all be seen and contained in the work ethic at the Indo Global Mandiri School of Sharia Economics and Business, Palembang.